Konstruksi Maskulinitas Global pada Majalah Pria di Indonesia dalam Persepsi Pria Metroseksual (Studi Kasus di Kota Medan) - Harmona Daulay (Jurnal Penelitian Kesejahteraan Sosial, 2014)
This research sees problems of global masculinity construction that appears in men’s magazine in Indonesia. Be conscious or not globalization era gives a strong effect upon Indonesian social order. This research started from researcher’s concern toward masculinity studies from masculine perspective itself in Indonesia which haven’t been critical detailed. The models of masculinity from masculine construction haven’t been found conceptually in Indonesia. The image that appears in mass media such as printed and electronic media are still about the image of men, which attach to the values of masculinity in western world. This research is conducted on 10 metrosexual men (informants) in the city of Medan, it uses interview technique and case study analyzes.The result of research shows the fact that metrosexual men in Medan come from upper middle class and have a lot money, so that it could support their needs of lifestyle. Metrosexual men often follow the latest fashion through global men’s magazine in Indonesia or from the western world. The result of research expresses the talks on global masculinity construction, which appear in men’s magazine show a very strong influencefrom western values. For example, from the fashion used by men to the lifestyle in western world. Most of the informants admitted the influence of global masculinity happens to Indonesian people especially to the informants in Medan. Even they don’t mind with masculinity construction in many facets such as in fashion, the informants admitted that they liked suits,which are formal attire in the western world. Most of the informants don’t agree to Asian style phenomenon masculinity, which appears from Korean Boy Band, according to them, Korean Boy Bands are very feminine and reduce the concept of existing Indonesia local masculinity.